ECONOMIC IMPACT ON DIGITAL TV BROADCAST MIGRATION FOR THE COMMUNITY IN THE UNEVEN DISTRIBUTION OF FREE SET TOP BOXES IN BANTEN PROVINCE - Angge Utomo; Dian Siska Pertiwi; Fernando Fernando; April Laksana (Jurnal Ekonomi, 2022)
Nowadays, many people are flocking to get used to living side by side with technology. The development of technology in the era of world globalization , the many developments of technological media and the migration of the transition from monologues to digital communication that occur in life. In this case, the public is confused by the termination of the Analog Switch Off (ASO) which began in November throughout Indonesia. The government has determined that the Jabodetabek Analog Switch Off (ASO) on November 2, 2022 will be completely extinguished. This study aims to determine the social impact that occurs in the field on the migration of analog to digital broadcasts has not been maximized by the Indonesian Broadcasting Commission Regions and related Communications and Informatics that handle broadcast migration. This research uses a qualitative approach. This approach is carried out to understand the phenomena about what the subject of study experiences holistically and with descriptions in the form of words and language, in the context of nature as well as by utilizing various scientific methods. This study uses a case study methodology, as a research that uses empirical evidence from one or more organizations and the researcher seeks to study problems in context. The Government of Indonesia through Communication and Informatics (Kemenkominfo) continues to socialize the transition of analog television broadcasts to digital television broadcasts and gradually migrates to digital TV, meaning that people who use analog no longer watch television shows. The Indonesian Broadcasting Commission of Banten Province stated that before the Analog Switch Off (ASO) will be implemented in November, the public already has a free Set Top Box from the government and the mux organizing media . The migration of analog television to digital television, it is possible that it will have a great influence on the development of television technology in the future, the era of digitalization there is convergence between broadcasting technologies ( broadcasting), communication technology (telephone), and internet technology